Pancreatic Adverse Events Associated With Immune Checkpoint Inhibitors: A Large-Scale Pharmacovigilance Analysis - Zhang, Yue; Fang, Yisheng; Wu, Jianhua; Huang, Genjie; Bin, Jianping; Liao, Yulin; Shi, Min; Liao, Wangjun; Huang, Na (Frontiers in Pharmacology, 2022)
Backgrounds: Immune checkpoint inhibitors (ICIs) are considered cornerstones of oncology treatment with durable anti-tumor efficacy, but the increasing use of ICIs is associated with the risk of developing immune-related adverse events (irAEs). Although ICI-associated pancreatic adverse events (AEs) have been reported in patients treated with ICIs, the clinical features and spectrum of pancreatic AEs are still not well-defined. Therefore, this study aimed to identify the association between pancreatic AEs and ICI treatments and to characterize the main features of ICI-related pancreatic injury (ICIPI) based on the Food and Drug Administration Adverse Event Reporting System (FAERS) database. Methods: Data from the first quarter of 2015 to the first quarter of 2021 in the database were extracted to conduct a disproportionality analysis. The selection of AEs related to the pancreas relied on previous studies and preferred terms from the Medical Dictionary for Regulatory Activities. Two main disproportionality analyses—the reporting odds ratio (ROR) and information component (IC)—were used to evaluate potential associations between ICIs and pancreatic AEs. Results: In total, 2,364 cases of pancreatic AEs in response to ICIs were extracted from the FAERS database, of which, 647 were identified as ICI-associated pancreatitis and 1,293 were identified as ICI-associated diabetes mellitus. Generally, significant signals can be detected between pancreatic AEs and all ICI treatments (ROR025 = 3.30, IC025 =1.71). For monotherapy, the strongest signal associated with pancreatitis was reported for anti-PD-L1 (ROR025 = 1.75, IC025 = 0.76), whereas that with diabetes mellitus was reported for anti-PD-1 (ROR025 = 6.39, IC025 = 2.66). Compared with monotherapy, combination therapy showed stronger associations with both ICI-associated pancreatitis (ROR025 = 2.35, IC025 = 1.20 vs. ROR025 = 1.52, IC025 = 0.59) and ICI-associated diabetes mellitus (ROR025 = 9.53, IC025 = 3.23 vs. ROR025 = 5.63, IC025 = 2.48), but lower fatality proportion. Conclusions: ICIs were significantly associated with the over-reporting frequency of pancreatic AEs, in which combination therapy posed a higher reporting frequency. Therefore, patients should be informed of these potential toxicities before ICI medications are administered.